Subcritical Water Extraction Technique for Selective Extraction of Pentacyclic Triterpenoids from Dry Loquat (Eriobotrya japonica) Leaves - Erasto Mlyuka (Science Faculty of Chiang Mai University, 2019)
Subcritical water extraction (SWE) is a novel alternative to conventional organic solvent extraction method (CE) for isolating corosolic acid (CA) and ursolic acid (UA) from loquat leaves (Eriobotrya japonica). SWE were performed in a subcritical water condition at a system pressure 4-10 MPa with the flow rate 33.33-50.00 mL/min, temperatures 100-250°C, and extraction time 5-90 min. The static mode, dynamic mode and static-dynamic mode for the extraction of CA and UA were optimized separately. LC/MS was employed for the quantification of total pentacyclic triterpenoids (PTTs). The results showed high yields of PTTs (25.02±0.71 mg/g) obtained at SWE conditions of 200°C, 41.67 mL/min and extraction time of 30 min (10 min static mode and 20 min dynamic mode) compared to 4 h extraction with CE (14.39±1.12 mg/g). CA (9.63±0.33 mg/g) and UA (15.04±0.81 mg/g) were the main PTTs obtained from dry loquat leaves at 180°C and 200°C, respectively using static-dynamic mode. Findings from this study suggest that SWE at 150 to 200°C, 10 MPa and 30 to 60 min might be a potential green technology to obtain PTTs from dry loquat leaves.